“New conditionality” in the EU’s “new generation” Agreements with Asian Countries - Kuźnar, Andżelika; Menkes, Jerzy Brunon (Review of European and Comparative Law, 2022)
The objective of the study is to verify the implementation, by the EU, of the treaties’ obligations to proliferate “non-trade” European values in agreements with Asian countries. The thesis of the study is that the EU with “new generation” agreements strengthens the cohesion of the western hemisphere and creates the conditions for its enlargement. An instrument supporting the strengthening and development of the western hemisphere is the policy of “change through trade” combined with the promotion of “free and fair trade”. We claim that this policy contributed to political change in the world – the expansion of international law, the principles of the UN Charter, and EU values. Influence beyond the parties to the agreements takes place, although formally the agreements only govern the relationship between the parties. This influence is the outcome of, among other things, demonstrating the implementation of the values and benefits of value-based cooperation. By agreements (FTAs, IPAs and political) with Asian countries, the network of connections among the states of the Western hemisphere is developed and the community of values reinforced. The institutionalisation of the community of values of EU-Asian countries also fosters the institutionalisation of ties among the democratic Asian countries.